1999
DOI: 10.1086/314966
|View full text |Cite
|
Sign up to set email alerts
|

The Role of B/T Costimulatory Signals in the Immunopotentiating Activity of Neisserial Porin

Abstract: A T cell-dependent immune response to group C meningococcal capsular polysaccharide (CPS) can be elicited when CPS is conjugated to the class 3 neisserial porin (CPS-porin). Treatment of CPS-porin-immunized mice with B7-2 blocking monoclonal antibody (MAb) caused a dramatic reduction in the CPS-specific IgG response, treatment with anti-B7-1 MAb had no effect, and concurrent blockade of B7-1 and B7-2 resulted in a synergistic abrogation of the CPS-specific IgG response while the CPS IgM response was unaffected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 45 publications
0
52
0
Order By: Relevance
“…Another group of animals was immunized with 10 µg of Nme PorB. For generation of anti-OVA antibodies, C57Bl/6 mice (n=5) and C3H/HeJ mice (n=4) (a mouse strain naturally non-responsive to LOS due to a mutation in the TLR4 gene [59]) were immunized with 10 µg of ovalbumin (OVA) alone or in the presence of 10 µg of Nlac PorB, 10 µg of Nme PorB [30] or with 200 µg of alum (Sigma) [60] as adjuvants. Ovalbumin was obtained from commercial chicken egg whites by freeze-drying followed by lyophilization and resuspension of the total egg white proteins in sterile PBS.…”
Section: Immunization Of Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of animals was immunized with 10 µg of Nme PorB. For generation of anti-OVA antibodies, C57Bl/6 mice (n=5) and C3H/HeJ mice (n=4) (a mouse strain naturally non-responsive to LOS due to a mutation in the TLR4 gene [59]) were immunized with 10 µg of ovalbumin (OVA) alone or in the presence of 10 µg of Nlac PorB, 10 µg of Nme PorB [30] or with 200 µg of alum (Sigma) [60] as adjuvants. Ovalbumin was obtained from commercial chicken egg whites by freeze-drying followed by lyophilization and resuspension of the total egg white proteins in sterile PBS.…”
Section: Immunization Of Animalsmentioning
confidence: 99%
“…Increased expression of CD86/CD80, MHC II and CD40 on the APC surface has been shown in response to porins from pathogenic Neisserial species (and other bacteria) [23,26,[30][31][32], as well as B cell proliferation and increased antibody production [33]. Activated APCs release specific cytokines (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Neisserial porins are the major outer membrane proteins expressed on the surface of Neisseria species and comprise Ͼ60% of the outer membrane protein content (6). Neisserial porins act as B cell mitogens (7) and are immunogenic in the absence of exogenous adjuvant, thereby enhancing immune responses to poorly immunogenic substances, such as small peptides (8) and capsular polysaccharides (9). Neisserial porins have thus been used as adjuvants in a number of vaccine preparations (8 -13).…”
mentioning
confidence: 99%
“…The mechanism of the adjuvant activity of neisserial porins involves up-regulation of the T cell costimulatory ligand, CD86, on the surface of APCs. In a murine vaccine model in which N. meningitidis PorB was directly conjugated to meningococcal capsular polysaccharide, administration of CD86 blocking Abs abrogated the ability of porin to induce anticapsular polysaccharide IgG (9).…”
mentioning
confidence: 99%
“…Interestingly, we and other investigators have demonstrated that these proteins act as immune stimulants and adjuvants (2)(3)(4) and can induce a T cell-dependent immune response against cell independent antigens (5-8). The mechanism of the adjuvant activity of neisserial porins recently has been elucidated, correlating with the porins' ability to upregulate the expression of the costimulatory molecule, B7-2, on the surface of B cells (and possibly other antigen-presenting cells) (6,8). Moreover, neisserial porins are potent B cell mitogens and act synergistically with CD40 or B cell receptor ligation to induce B cell proliferation and Ig secretion (6,9).…”
mentioning
confidence: 99%